2009
DOI: 10.1084/jem.20090639
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid can enhance conversion of naive into regulatory T cells independently of secreted cytokines

Abstract: It has been reported that retinoic acid (RA) enhances regulatory T (T reg) cell conversion by inhibiting the secretion of cytokines that interfere with conversion. This report shows that these conclusions provide a partial explanation at best. First, RA not only interfered with cytokine secretion but also with the ability of these cytokines to inhibit T reg cell conversion of naive T cells. Furthermore, RA enhanced conversion even in the absence of inhibitory cytokines. The latter effect depended on the RA rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 30 publications
9
123
2
Order By: Relevance
“…Others have already argued how unlikely it is that a single molecule or pathway would explain the functional differences between immature and mature T cells (37). Importantly, our findings are also compatible with the notion that mucosa, a microenvironment rich in TGF-β and retinoic acid where inflammation is maintained at check, efficiently supports the differentiation of Tregs (31,38). The concept brought about by our analysis is that systemic peripheral conversion (i.e., in situations of limited retinoic acid and TGF-β and/or in inflammatory context) is restricted to RTEs.…”
Section: Discussionsupporting
confidence: 89%
“…Others have already argued how unlikely it is that a single molecule or pathway would explain the functional differences between immature and mature T cells (37). Importantly, our findings are also compatible with the notion that mucosa, a microenvironment rich in TGF-β and retinoic acid where inflammation is maintained at check, efficiently supports the differentiation of Tregs (31,38). The concept brought about by our analysis is that systemic peripheral conversion (i.e., in situations of limited retinoic acid and TGF-β and/or in inflammatory context) is restricted to RTEs.…”
Section: Discussionsupporting
confidence: 89%
“…Recent reports showed that CNS1 contains binding sites for transcription factors NFAT, Smad3, and RAR/RXR. Further studies revealed that RA enhances TGF-␤ signaling by increasing the expression and phosphorylation of Smad3 (146,217). Indeed, RA actions involve the binding of RAR/ RXR to CNS1.…”
Section: Molecular Mechanism Of Ra-induced Foxp3 Expressionmentioning
confidence: 99%
“…atRA inhibits expression of IL-6Ra on naive T cells, which, together with TGF-b, promotes differentiation of naive T cells into Th17 cells; IL-6 has the reciprocal effect of inhibiting the expression of RARa (41,59,60). Moreover atRA acts through RARa in activated CD4 + T cells to promote the expression of Foxp3, independently of the cytokine IL-2, the TGF-b-signaling molecules SMAD3 and SMAD4, and the transcription factors STAT3 and STAT5 (59,61,62). Furthermore, RA enhances the expression of arginase 1 in DCs in vitro, an enzyme known to promote the production of Tregs (63).…”
Section: Ra In Innate Immunity Including Its Influence On Apcsmentioning
confidence: 99%
“…high memory T cells, the effect of RA on iTreg conversion is significantly decreased (59,65). Interestingly, in the GALT, but not in lymph nodes and spleen, activation of CD44 high T cells in the absence of TGF-b leads to the expression of the RA-degrading enzyme CYP26B1, which, in turn, inhibits the expression of CCR9 on T cells (67).…”
Section: Ra In Innate Immunity Including Its Influence On Apcsmentioning
confidence: 99%